Birth outcome and HIV infection among labouring women in Assosa Hospital, Southwest Ethiopia. - Chekol, Asaye (The Ethiopian Journal of Health Development, 2016)
Abstract Background: Perinatal mortality rate is a sensitive indicator of quality of care provided to women in pregnancy, at andafter childbirth and to the newborns in the first week of life. Regular prenatal audit would help in identifying all thefactors that play a role in causing prenatal deaths and thus help take appropriate interventions to reduce the avoidableonce, at least. Knowledge of mothers’ HIV positive status provides an entry point for appropriate care of the mothers,HIV exposed infants and other family members including children. Objectives: To assess birth outcomes and the magnitude of HIV infection among labouring mothers in Assosahospital. Method: An institution-based cross-sectional survey was conducted in Assosa hospital from September 2008 toAugust 2009. A total of 581 labouring women were interviewed using a pretested structured questionnaire.Results: Data was obtained from 581 mothers. HIV infection among labouring women was 6.5%. Mothers, who hadprimary education [AOR=4.76, 95%CI= 1.81-12.52], no formal education [AOR=3.05, 95%CI= 1.08-8.64], mothers with two or more pregnancies [AOR=2.64, 95%CI= 1.08-6.49], and Muslims [AOR=0.32,95%CI= 0.13-0.82] were theindependent predictors of HIV infection. There were 525 live births. The prenatal deaths were 69, making an overallprenatal mortality of 119 per 1000 total births. Bivariate analysis showed that rural women, women who had no ANCvisit, mothers aged 30 years and above, with no formal education, housewives, Berta women of in ethnic group andMuslim were crudely associated with higher risk of prenatal mortality.Conclusion: The study identified high level of perinatal mortality and HIV infection. This study calls for effectiveantenatal care, delivering service, and a coordinated referral system and community interventions including HIVcounseling, testing (VCT), treatment and support. [Ethiop. J. Health Dev. 2011;25(1):10-16]